The influence of iron impurities on the compression behaviour of Al-2.24Mg-2.09Li alloy - Kozina F.; Zovko-Brodarac Z.; Petrič M.; Penko A. (Journal of Mining and Metallurgy. Section B: Metallurgy)
As a major impurity element in aluminium-lithium (Al-Li) alloys, iron (Fe) reduces formability, fracture toughness, and fatigue resistance by solidifying into Al6Fe and Al3Fe particles. The research was performed in order to estimate the influence of Fe impurities on the compression behaviour of Al-2.24Mg-2.09Li alloy. The investigation was performed on the samples in as cast and solution hardened condition. The solution hardening was applied to improve the mechanical properties by dissolving intermetallic particles and enriching αAl matrix with Mg. However, the higher strength properties and temperature increase during the compression testing were observed in as cast condition. Microstructural investigation revealed significant differences in microstructure changes between the samples in as cast and solution hardened condition. In as cast sample the barrelling effect led to the unequal deformation and surface texture development. The eutectic Al3Fe particles located in the αAl interdendritic areas did not significantly impact microstructure changes. Although the solution hardening led to enrichment of αAl matrix with Mg and Fe, the Al3Fe particles were not dissolved. The coarse morphology of Al3Fe particles and location at the grain boundaries of αAl grains contributed to low energy intergranular fracture. The fracture nucleation and propagation across the grain boundaries resulted in lower strength values.